The role of secondary cyclones and cyclone families for the North Atlantic storm track and clustering over western Europe - Priestley, Matthew D.K.; Dacre, Helen F.; Shaffrey, Len C.; Schemm, Sebastian; id_orcid:0 000-0002-1601-5683; Pinto, Joaquim G. (Wiley, 2020)
ISSN:0035-9009 ISSN:1477-870X